Growth and poverty : the development experience of Bangladesh - Ahmed, Sadiq; Mahmud, Wahiduddin (The University Press, 2006)
Contributed articles presented at a seminar held in Dhaka during June 26-27, 2003 organized at Bureau of Economic Research, University of Dhaka and with support of World Bank.